31 The prognostic value of transient elastography: a single centre irish study. (5th April 2017) - Naimimohasses, S; El-Sherif, O; O'Connell, J; Hynes, B; Irish, H; Quinn, C; Miggins, SJ; MacCarthy, F; Kevans, D; Iqbal, M; McKiernan, S; Norris, S
Abstract : Background: Transient elastography (TE) has facilitated the rapid and non-invasive assessment of hepatic fibrosis. Recent studies have signified its utility in identifying patients with early clinically significant portal hypertension (CSPH), providing valuable prognostic information and has been incorporated in the Baveno VI recommendations. Aim: The aim of this study was to assess for features of CSPH and evaluate the clinical outcomes in patients with TE scores of ≥10 kPa. Method: A retrospective review was performed on all patients attending the Hepatology Department in St. James' Hospital with valid TE measurements≥10 kPa using an ECHO-sens Fibro-scanner with a M2 probe. Results: A total of 384 (18%) patients had transient elastography scores≥10 kPa. The most common aetiologies were HCV n=237 (61.7%) and NAFLD n=45 (11.7%). A TE score of ≥30 kPa was highly predictive of numerous composite endpoints: liver-related hospital admissions OR8.6 (95% CI 4.1 to 18.0), decompensation OR12.7 (95% CI 5.47 to 29.3) and death OR8.61 (95% CI 2.8 to 26.5). The Baveno VI criteria demonstrated a good predictive value for the presence of oesophageal varices OR2.7 (95% CI 1.39 to 5.26), however, the negative predictive value was poor 79.1% in our mixed patient population. Conclusions: A TE score threshold of ≥30 kPa demonstrated good predictive value for identifying at risk patients. Although the Baveno VI criteria was useful for the discrimination of patients at risk of developing varices, other factors may also need to be considered in order to improve the negative predictive value.